Do discounts livestream and bundle offers triggers TikTok user unplanned purchases? - Gita, Leiya; Fauzan, Rizky; Pebrianti, Wenny; Juniwati, Juniwati; Jaya, Arman (Institute of Computer Science (IOCS), 2024)
TikTok is a medium of information, entertainment, and communication. TikTok's new feature is TikTok shop. Live streaming is here for consumers who like direct interaction with sellers via real-time video. The objective of this study is to examine the impact of discounts on livestream selling and bundle offers on unplanned purchases TikTok users through positive emotion. This research method uses causality. Data was distributed via questionnaire to 205 people who shopped online on selected TikTok livestream using a purposive sampling method. The research results based on SEM AMOS 22 calculations show that the value of discounts on livestream selling has a positive and significant impact on unplanned purchases. TikTok livestream, bundle offers have a positive and significant impact on unplanned purchases, TikTok livestream, positive emotion can mediate the relationship between discounts on livestream selling on unplanned purchases, positive emotion can mediate the relationship between bundle offers on unplanned purchases and positive emotion has a positive impact when making unplanned purchases on TikTok livestream consumers. It is hoped that the results of this research will provide a valuable contribution to online business players in their efforts to increase marketing effectiveness in the developing livestream-selling sector, which is currently experiencing fast growth.